Issues and propositions on the improvement of doctoral education - Tatyana Lipai; Mariam Gevorgyan (Jan Dlugosz University, 2020)
Higher education institutions (HEIs) in Armenia and Belarus have been conducted doctoral and postgraduate programs since Soviet Union times. In both countries consisted of two successive scientific (research) degrees: Candidate of Sciences and Doctor of Sciences. The main purpose of research education has been the creation of new investigation; moreover, it gave bigger importance to the results of scholarship rather than formation of scholars with specific knowledge, capacities, and skills, including teaching skills for higher education, dealing with modern technologies, and so on. In contemporary post-industrial societies, knowledge becomes outdated very quickly, making the training of versatile, innovative doctoral candidates a high priority. Their future career and employment opportunities are not limited to scholarly endeavors or teaching activities in traditional academic environment. The new generation of researchers should be competent not only in their professional area, but also have general broad preparedness, including communication, management and entrepreneurial skills. Our article also offers a mixed-method perspective on the investigation of determinants of effectiveness in quality assurance at higher education institutions.